"Teaching students like me:" Bilingual authorization candidates, motivations, and California's bilingual education renaissance. Issue 4 (2nd October 2022) - Sawyer, Adam; Almaguer, Jasmin
ABSTRACT: Emerging from nearly two decades of language suppression wrought by Proposition 227, a Bilingual Education Renaissance is underway in California as new programs proliferate at a much faster clip than the state can produce certified bilingual teachers. California's policy shift is built upon an officially stated view of bilingualism as a resource beneficial for student academic success and global economic competitiveness. While the stated goals of public policy are clear, less known is what motivates educators aspiring to serve these new programs and how these individuals have been personally affected by the language restrictions of Proposition 227. Through analysis of surveys and autobiographical writing collected from bilingual authorization candidates in Central California, we explore the motivations of these budding bilingual educators, compare and contrast these motivations to those of state policy, and examine in autobiographical detail their ethnolinguistic experiences. We find that bilingual certification candidates – in contrast to the explicit economic considerations of the state–are overwhelmingly driven by a sense of advocacy and personal identification with the ethnolinguistic experiences and struggles of emergent bilingual students. We discuss implications for public policy, candidate recruitment, and the design of program content that is supportive and leveraging of candidate ethnolinguistic experiences and assets.